Upaya Meningkatkan Keaktifan Pembelajaran Siswa Kelas XI ATPH A SMKN 1 Bawen dengan Implementasi Pendekatan Pembelajaran Berdiferensiasi - Safitri, Ulin Nur; Nurwahyunani, Atip; Cahyati, Zubaidah Gesit (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The main problem underlying this research is the lack of activeness of class XI ATPH A SMKN 1 Bawen students in participating in learning. This is because the characteristics of students learning styles are variated so that if teachers don’t accommodate the needs of their learning styles, students will be reluctant to pay attention the learning level of use of learning technology; motivation to learn mathematics and even have difficulty understanding the lesson. The method used in this research is descriptive qualitative. The results of this research are that researchers can find out the teacher's strategy to increase the activeness of class XI ATPH A students in learning, namely by presenting differentiated learning content. The content differentiation strategy is provided by the teacher so that students can explore insight and understanding regarding the material being taught. Student activeness in learning will appear automatically if students understand learning well because their learning needs have been fulfilled.